Fragmentation of Modern Artistic Narrative (English-Language Prose) - G. I. Lushnikova; T. Yu. Osadchaya (Научный диалог)
The question of the role, forms and functions of fragmentation of modern artistic narra tive is considered. The results of the analy sis of the fragmentary narrative of the works of contemporary  English-speaking  authors (J.   Barnes,   D.   Mitchell,   M. Cunningham, I. Banks, J. Franzen, S. Faulks, J. Eugenides, A. Smith, J. McGregor and others) are presented. The relevance of the study is due to the fact that in the modern literature of the postmodernist direction, nonlinearity of narration, deliberate mixing of temporal, local, descriptive and other layers are becoming widespread, practically becoming the norm. The novelty of the research is seen in the fact that the fragmentation of a literary text is studied at different levels — compositional, content-thematic, plot, ideological-figurative, genre, narrative, chronotopic. It has been proved that the forms of implementation of fragmentariness are quite diverse: irregular division of the text, heterogeneity of themes and ideas, lack of linear development of the plot, combination of elements of different genres, the presence of internal polystylism, the use of different types of narration and narrator, violation of the unity of the chronotope. The analysis of specific material showed that the functions of a fragmentary narrative are determined by each specific context, the leading ones being the impact on the reader, the management of his attention, the placement of accents according to the writer's intention, the creation of the impression of authenticity and reliability.